A Distributed Architecture Supporting Heuristic and Metaheuristic Optimization Methods - Costa, Celso M. da; Dotti, Fernado L.; Mathias, Eder N.; Müller, Felipe M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This paper presents a distributed software architecture that allows the cooperation among research institutions in the field of Operations Research. It has as main aims to share existing algorithms for optimization problems, to allow the easy testing of these algorithms with existing instances, and to share computational power among the cooperating institutions. This is achieved respecting the autonomy and heterogeneity of the cooperating institutions. The five functional blocks that build the architecture are discussed here and also a study case of a Parallel Memetic Algorithm to solve the Traveling Salesman Problem running on this environment is analysed.